Perencanaan Sistem Interkoneksi Jaringan Listrik Kabel Bawah Laut di Propinsi Maluku - Johanis Tupalessy; Rini Nur Hasanah; Hadi Suyono (Jurnal EECCIS, 2015)
Power system stability analysis is required to determine the performance of a power system. In this paper an analysis is performed on the interconnection system of Ambon, Haruku, and Saparua islands in Maluku region of Indonesia. The analyses in this research include load-flow analysis, steady-state and transient stability analysis, rotor angle, frequency and voltage stability during fault conditions, both before and after the interconnection. Critical clearing time has been analyzed to determine the system performance after a fault interruption. Results of steady-state stability analysis show a voltage profile improvement of 1.163%. The results also show that after interconnection better condition of rotor angle, frequency and voltage, and faster recovery time are obtained. Critical clearing time after interconnection is 0.58 seconds longer than before the interconnection.Index Terms—Interconnection, voltage profile, load flow, system stability.